CURRICULAR EXTENSION IN PSYCHOLOGY: CHALLENGES AND EXPERIENCES IN ARTICULATION WITH THE CLASSROOM (CIPEEX, 2025)
This experience report discusses the challenges and strategies developed by the Psychology program at UniEvangélica in implementing curricular extension, as established by Resolution CNE/CES nº 07/2018. The main challenge identified has been the creation of extension activities that simultaneously generate positive impacts on the community and enhance student learning, while being adapted to the concrete reality of courses and classrooms. To this end, actions have been proposed that integrate theory and practice, with emphasis on themes such as mental health, public health promotion, social inclusion, and well-being. These experiences have enabled students to develop professional and civic competencies, in addition to broadening their understanding of the social role of Psychology. For the community, the activities have provided spaces for support, listening, and intervention, generating concrete benefits in participants’ daily lives. It was also observed that integrating extension into courses strengthens the bond between university and society, allowing the educational process to become more dynamic, participatory, and connected to local demands. The conclusion is that, although challenges remain, curricular extension has been consolidated as a highly relevant formative space, contributing both to the integral training of psychologists and to meaningful social transformations.
Keywords: university extension; Psychology; classroom; community; integral education.